Pengaruh Masa dan Tempat dalam Penyusunan Tafsir Al-Azhar - Elit Ave Hidayatullah; Deki Ridho Adi Anggara; Mahmud Rifaannudin; Mujib Abdurrahman (Universitas Darussalam Gontor, 2022)
In contrast to the previous centuries of the XX century, the century of young people with the spirit of coming out of stagnant thinking has indirectly stimulated the attention of scholars in studying interpretations and compiling works of interpretation with various methods, patterns and styles. Tafsir al-Azhar is one of the largest interpretations compiled by Hamka, Hajj Muhammad Karim Amrullah. This article attempts to critically examine whether there is an influence of time and place in the preparation of the Tafsir al-Azhar. For this reason, historical methods and critical analysis will be used to show the figure of Hamka and his interaction with the socio-culture of the Minang people in particular and Indonesia in general. At the same time, it is used to analyze the Tafsir al-Azhar with regard to the influence of the time and place in the work. The result is that Hamka in explaining the verses of the Qur'an sometimes takes wisdom from the customs of a society that signify the place and explain also from the period of development of political turmoil after Indonesian independence and the renewal of the thoughts of Islamic figures that signify time, furthermore,the place and time have exerted influence in compiling the Indonesian interpretation work